Learning mathematic in bahasa melayu for early childhood using mobile application [electronic resource] - Nylia Zildjiani 1992-, author (2013)
Project Paper (Sarjana Muda Sains Komputer (Sistem Maklumat)) - Universiti Teknologi Malaysia, 2013